Clinically relevant cranio-caudal patterns of cervical cord atrophy evolution in MS - Rocca, Maria Assunta; Valsasina, Paola; Meani, Alessandro; Gobbi, Claudio; Zecca, Chiara; Rovira, Alex; Montalban, Xavier; Kearney, Hugh; Ciccarelli, Olga; Matthews, Lucy; Palace, Jacqueline; Gallo, Antonio; et al. (Neurology, 2019)
To characterize the distribution and regional evolution of cervical cord atrophy in patients with multiple sclerosis (MS) in a multicenter dataset.
Gesehen am 01.04.2020